Green livability: the impact mechanism of aging-friendly recreational landscapes in residential green spaces - Wang, Fanglong; Hussain, Norhuzailin; Abdul Aziz, Faziawati (Taylor and Francis, 2025)
Residential green spaces (RGS) are essential environmental elements that enhance the quality of life for the elderly, yet the impact mechanism of their recreational landscape(RL) characteristics on elderly satisfaction remains underexplored. Based on the American Customer Satisfaction Index (ACSI) model, this study constructs a theoretical framework to evaluate elderly satisfaction with RL in RGS, incorporating recreational intention (RI), perceived recreational landscape quality characteristics (PRLQC), perceived recreational landscape value(PRLV), and recreational satisfaction(RS) as core latent variables. Using Lianyungang, China, as the research area and a targeted sampling method, the study empirically examines the relationships among these variables. The results indicate that RI, PRLQC, and PRLV have a significant positive impact on RS. Notably, RI not only directly influences RS but also exerts an indirect effect through the mediating roles of PRLQC and PRLV. Further analysis reveals that PRLQC play a crucial mediating role in the overall pathway, making it a key factor affecting elderly RS. This study validates the applicability of the optimized ACSI model in evaluating aging-friendly RL in RGS, expands the scope of aging research, and provides scientific evidence and practical guidance for urban green space planning and aging-friendly landscape optimization.